2012
DOI: 10.14723/tmrsj.37.365
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of amphiphilic polyphosphoester ionomers for surface modification of small unilamellar phospholipid vesicles

Abstract: Bone-specific drug delivery is important for the treatment of osteoporosis and osseous metastases. Bisphosphonates are currently the major drugs used in this treatment. The clinical action of bisphosphonates on bone has been clarified and the molecular structure has been improved in order to obtain higher efficiency. By mimicking the chemical structure of bisphosphonate, we have synthesized polyphosphoester ionomers to modify the surface of phospholipid vesicles as novel bone-specific drug carriers. The ring-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It was clarified that the stability of phospholipid bilayer structure was influenced by not only cholesterol but also by polyphosphoester ionomers. However, the destabilization of CH‐PHE(17) was also observed when the fraction of CH‐PHE(17) was greater than 3 mol % 42. It has been reported that CF release was enhanced under acidic conditions because the hydrophobicity of CF was increased in that condition 43.…”
Section: Resultsmentioning
confidence: 96%
“…It was clarified that the stability of phospholipid bilayer structure was influenced by not only cholesterol but also by polyphosphoester ionomers. However, the destabilization of CH‐PHE(17) was also observed when the fraction of CH‐PHE(17) was greater than 3 mol % 42. It has been reported that CF release was enhanced under acidic conditions because the hydrophobicity of CF was increased in that condition 43.…”
Section: Resultsmentioning
confidence: 96%